Fusogenic Viruses in Oncolytic Immunotherapy - Krabbe, Teresa (Cancers (Basel), 2018)
Oncolytic viruses are under intense development and have earned their place among the novel class of cancer immunotherapeutics that are changing the face of cancer therapy. Their ability to specifically infect and efficiently kill tumor cells, while breaking immune tolerance and mediating immune responses directed against the tumor, make oncolytic viruses highly attractive candidates for immunotherapy. Increasing evidence indicates that a subclass of oncolytic viruses, which encodes for fusion proteins, could outperform non-fusogenic viruses, both in their direct oncolytic potential, as well as their immune-stimulatory properties. Tumor cell infection with these viruses leads to characteristic syncytia formation and cell death due to fusion, as infected cells become fused with neighboring cells, which promotes intratumoral spread of the infection and releases additional immunogenic signals. In this review, we discuss the potential of fusogenic oncolytic viruses as optimal candidates to enhance immunotherapy and initiate broad antitumor responses. We provide an overview of the cytopathic mechanism of syncytia formation through viral-mediated expression of fusion proteins, either endogenous or engineered, and their benefits for cancer therapy. Growing evidence indicates that fusogenicity could be an important feature to consider in the design of optimal oncolytic virus platforms for combinatorial oncolytic immunotherapy.